UMP publisher’s book ‘Lean Manufacturing Tools’ won best text book in Iran - Shalfarina, Shahriman (Pejabat Naib Canselor, 2016)
A book published by UMP Publisher titled, ‘Lean Manufacturing Tools’ was picked as the best text book in industrial engineering by Islamic Azad University, Iran, in a publication award event organised by the university on January 20, 2016.